A novel 3D simulation model for investigating liquid desiccant dehumidification performance based on CFD technology. (15th April 2019) - Tao, Wen; Yimo, Luo; Lin, Lu
Highlights: A novel 3D CFD simulation model was developed for falling film dehumidifier. The new model was validated by experiments with high accuracy. Parametric study was carried out to study the influences of different parameters. Mass transfer enhancement approaches were put forward accordingly. Abstract: Previous 2D CFD simulation models fail to elaborate the actual simultaneous flow and dehumidification process in liquid desiccant cooling system. Accordingly, the present study successfully developed a novel 3D simulation model for investigating the liquid desiccant dehumidification performance of a falling film dehumidifier. The penetration mass transfer model was implemented in the simulation to account for the interfacial dehumidification process. Experimental system was built for the model validation and the results indicated that the newly developed 3D CFD model could predict the absolute moisture removal accurately with an average deviation of 7%. Parametric study revealed that the dehumidification performance was closely related with air humidity, velocity, solution temperature, centration, temperature and contact angle but seldom affected by air temperature. The simulation results also indicated that falling film of liquid desiccant shrank gradually along the flow direction, leading to an inhomogeneous water vapor absorption process in the dehumidifier. Intense water vapor absorption occurred at the phase interface, resulting in large solution concentration gradient and humidity content in the zone near the air/liquid contact interface. However, minor mass transfer occurred in other zones mainly in the form of diffusion. Accordingly, several heat/mass transfer enhancement approaches, i.e. structural modifications and surface modification, were proposed to improve the flow turbulence and to enlarge the falling film wettability. The newly proposed 3D simulation model and dehumidification enhancement approaches are meaningful for the design and operation of liquid desiccant cooling system.